2017
DOI: 10.1016/j.celrep.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Lhx2 Expression in Postmitotic Cortical Neurons Initiates Assembly of the Thalamocortical Somatosensory Circuit

Abstract: Cortical neurons must be specified and make the correct connections during development. Here, we examine a mechanism initiating neuronal circuit formation in the barrel cortex, a circuit comprising thalamocortical axons (TCAs) and layer 4 (L4) neurons. When Lhx2 is selectively deleted in postmitotic cortical neurons using conditional knockout (cKO) mice, L4 neurons in the barrel cortex are initially specified but fail to form cellular barrels or develop polarized dendrites. In Lhx2 cKO mice, TCAs from the thal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 36 publications
7
32
0
Order By: Relevance
“…Lmo4, a member of the LIM-only (LMO) subfamily of LIM domain–containing TFs, was first identified to participate in embryogenesis (Kenny et al, 1998). Some studies showed that Lmo4 is required for neural tube closure (Lee et al, 2005) and assembly of the thalamocortical somatosensory circuit (Wang et al, 2017a). It has been reported that Lmo4 is expressed in the thymus and is implicated in the oncogenesis of T cell acute leukemia (Grutz et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Lmo4, a member of the LIM-only (LMO) subfamily of LIM domain–containing TFs, was first identified to participate in embryogenesis (Kenny et al, 1998). Some studies showed that Lmo4 is required for neural tube closure (Lee et al, 2005) and assembly of the thalamocortical somatosensory circuit (Wang et al, 2017a). It has been reported that Lmo4 is expressed in the thymus and is implicated in the oncogenesis of T cell acute leukemia (Grutz et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to many well-established NE-related TFs identified in this analysis (such as SOX2 and ASCL1), it also predicted many neuronal differentiation related TFs that might also be involved in NED. For instance, expression of LHX2 has previously been showed to confer neuronal competency for activity-dependent dendritic development of cortical neurons [64], but its role in NED of prostate cancer remains undetermined and need future studies to clarify their specific roles.…”
Section: Identifying Ned-associated Transcription Factor Regulatory Nmentioning
confidence: 99%
“…These studies have shown that synaptic release of glutamate from the thalamocortical axons is required for the assembly of L4 neurons into barrels and dendritic polarization towards these axons, in particular via activation of NMDA receptors and metabotropic glutamate receptors17. In addition, several transcription factors, including Lhx2, Npas4, Zbtb20 function to polarize L4 dendrites towards incoming VB axons in S1 (refs 79, 80, 81), and Btbd3 has a similar role in V1 (ref. 82).…”
Section: Developmental Emergence and Plasticity Of Neocortical Circuitsmentioning
confidence: 99%